Recoveries of 15N-labelled fertilizers (chicken manure, mushroom compost and potassium nitrate) in arable topsoil after autumn application to winter cover crops - Holbeck, Britta; Amelung, Wulf; Wolf, Andreas; Südekum, Karl-Heinz; Schloter, Michael; Welp, Gerhard (Soil & tillage research, 2013)
•Soil texture and soil organic carbon content do not affect 15N dynamic.•15N release depends on fertilizer (chicken manure, mushroom compost, mineral N).•Mustard intercropping is a tool to enhance N efficiency. Frequently, organic fertilizers are applied to maintain or to increase soil fertility and plant yields. However, as the N availability of organic fertilizers is difficult to calculate, applied fertilizer N may be subject to loss, particularly through leaching. The objective of this study was to evaluate the fate of fertilizer N from two common organic manures (chicken manure, mushroom compost) in arable topsoil during one winter cover cropping and cropping season. For this purpose, 15N-labelled fertilizers were produced by feeding chicken with 15N-labelled maize pellets and by incubating a mushroom substrate with 15N-labelled mineral fertilizer, respectively. Thereafter, the 15N uptake by a mustard winter cover crop, its release to the main crop (sugar beet), and its retention in soil were investigated in two differently textured soils under otherwise identical conditions during a period of 400 days. Mineral K15NO3 fertilizer served as control. In the surface soil (0–10cm), only 20–40% of the applied 15N was recovered after the first 50–60 days, which was the period of mustard growth. Thereafter, the amount of 15N recovered in the soil increased again until day 259, reflecting the re-release of the fertilizer N from the winter cover crop in all treatments. The fertilizer N recovery in the winter cover crop itself was highest for mushroom compost (60%), followed by mineral fertilizer (50%) whereas it was almost not detectable for chicken manure (3%). Soil texture did not affect the overall retention of the fertilizer N in soil, and even after 400 days we recovered 67% of the fertilizer N from mushroom compost, 37% from chicken manure and 28% from the mineral fertilizer (0–30cm). The following main crop, sugar beet, still utilized between 7 and 13% of the initial fertilizer addition from the previous summer. We conclude that mustard winter cover cropping after organic fertilization is efficient in retaining available N during winter time, and mushroom compost is better than mineral N-fertilizer and chicken manure in respect of being a slow and sustainable N fertilizer source for the plants at reduced N losses.